2009
DOI: 10.1002/hed.21044
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of percutaneous endoscopic gastrostomy tubes versus nasogastric tubes for enteral feeding in patients with head and neck cancer undergoing (chemo)radiation

Abstract: Background. Percutaneous endoscopic gastrostomy (PEG) tubes have largely replaced nasogastric tubes (NGTs) for nutritional support of patients with head and neck cancer undergoing curative (chemo) radiotherapy without any good scientific basis.Methods. A prospective study was conducted to compare PEG tubes and NGTs in terms of nutritional outcomes, complications, patient satisfaction, and cost.Results. There were 32 PEG and 73 NGT patients. PEG patients sustained significantly less weight loss at 6 weeks post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
166
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(180 citation statements)
references
References 17 publications
11
166
0
2
Order By: Relevance
“…Prophylactic feeding tube placement compared with a reactive approach has been reported in several studies to reduce the extent of treatment related weight loss and hospital admissions 4,9,10 , and to lead to improved short term quality of life 12,13 . However, long term swallowing function is a major late toxicity associated with treatment, and should be a major factor in selecting the optimal strategy to support nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prophylactic feeding tube placement compared with a reactive approach has been reported in several studies to reduce the extent of treatment related weight loss and hospital admissions 4,9,10 , and to lead to improved short term quality of life 12,13 . However, long term swallowing function is a major late toxicity associated with treatment, and should be a major factor in selecting the optimal strategy to support nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This remains a contentious area, and both approaches to enteral feeding have advantages and drawbacks. Several studies have suggested that the use of prophylactic gastrostomy placement is associated with a reduction in weight loss during treatment, a lower rate of hospitalisation 4,[9][10][11] , and improved quality of life during and soon after treatment 12,13 . Disadvantages of prophylactic gastrostomy placement prior to treatment include the possibility that the tube will not be required, a small risk of tube-related morbidity 14 , and the uncertain influence upon long term enteral feeding dependency rates 6,[9][10][11]15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ASCO guidelines [137] • Regarding the enteral nutrition, there were significantly more infections in the PEG group (66%) compared to the NGT group (30%) p = 0.001 in the prospective study of Corry et al [124], but the difference of pneumonia between the two groups (PEG = 31.3% vs. NGT = 30%) was statistically insignificant. In fact, the majority of infections in the PEG group were at the PEG site (31%: 10/32).…”
Section: -The Evaluation Of the Suspected Infection Sourcementioning
confidence: 98%
“…The main infection sources in HNCPs are the respiratory tract, the oral cavity, and medical devices such as central venous catheters (CVCs) [122], especially total implanted access ports [123], gastrostomy [124], and tracheostomy [47].…”
Section: -The Evaluation Of the Suspected Infection Sourcementioning
confidence: 99%